Clinicopathologic Parameters Related to Recurrence and Locoregional Metastasis in 180 Oral Squamous Cell Carcinomas. (February 2014) - Montebugnoli, Lucio; Gissi, Davide Bartolomeo; Flamminio, Federica; Gentile, Luciano; Dallera, Vittorio; Leonardi, Elisa; Beccarini, Tommaso; Foschini, Maria Pia
Lymph node metastasis (LNm), local recurrence (LR), and second primary tumor (SPT) after primary surgery for oral squalmous cell carcinoma (OSCC) have been considered poor prognostic entities in terms of survival rate. The purpose of this study was to identify the clinicopathologic parameters significantly related to LNm, LR, and SPT. Records from 180 patients who underwent radical surgery for OSCC were retrospectively reviewed. Perineural invasion was significantly related to LNm (18% vs 8%) and LR (15% vs 5%), while the status of the surgical margin (10% in case of clear margins, 18% close margins, and 24% involved margins), namely epithelial precursor lesions (43%) was an independent factor influencing SPT. Perineural invasion proved a good prognostic factor for early events, either LNm or LR, while a surgical margin width less than 5 mm or with epithelial precursor lesions may be considered a risk factor for late events such as SPT.